Fiscal Autonomy and Self-Determination - Gabriel Loumeau; Christian Stettler (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper studies the equilibrium effects of local fiscal autonomy accounting for benefits from self-determination. It proposes a quantifiable structural equilibrium framework in which imperfectly mobile heterogeneous households sort themselves across jurisdictions under endogenous public good provision. We calibrate the framework to fit the economic and geographic characteristics of the Canton of Bern using household-level data. In particular, we exploit quasi-natural policy variation in voting rights to quantify benefits from self-determination, and employ machine learning methods to accurately represent the local political process. We find that restricting local fiscal autonomy decreases welfare for (almost) all households.
Keywords: H71; H77; R51; 330; fiscal autonomy; self-determination; decentralization; household; equilibrium; quasi-natural variation